Pioglitazone treatment in type 2 diabetes mellitus when combined with portion control diet modifies the metabolic syndrome - Gupta, A. K. (2009)
BACKGROUND: Treatment with thiazolidinediones (TZDs) produces weight gain. OBJECTIVE: To test whether a portion control diet could prevent weight gain during treatment with pioglitazone in patients with type 2 diabetes mellitus (T2DM). DESIGN: This 16-week randomized, open-label, parallel arm study compared three groups: (i) pioglitazone plus the American Diabetes Association diet (Pio + ADA); (ii) pioglitazone plus a portion control weight loss diet (Pio + PC); (iii) metformin plus the American Diabetes Association diet (Met + ADA). All participants received the same advice about calorie reduction, lifestyle change and exercise. METHODS: Fifty-one men and women with T2DM, naive to TZDs, were randomized to a 16-week study. Pioglitazone (Pio) was titrated to a dose of 45 mg/day and metformin (Met) to a dose of 2 g/day. Fasting blood was collected for lipids, insulin and glycosylated haemoglobin A1c (HbA1c) at baseline and 16 weeks. RESULTS: Forty-eight of fifty-one randomized subjects completed the study. Patients treated with Pio + ADA gained 2.15 ± 1.09 kg (mean ± SD) compared with a weight loss of 2.59 ± 1.25 kg (p < 0.05) in the Pio + PC group, and aweight loss of 3.21 ± 0.7 kg (p < 0.05) in the Met + ADA group. Waist circumference and visceral adipose tissue decreased significantly more in the Pio + PC group than in the Pio + ADA group. High-density lipoprotein cholesterol levels were significantly increased in the Pio + PC group compared with the Met + ADA group. Pioglitazone reduced insulin resistance (homeostasis model assessment of insulin resistance (HOMA-IR)) more than metformin. No significant differences between groups were seen for glucose, insulin, HbA1c or low-density lipoprotein cholesterol levels. CONCLUSIONS: Pio + PC, prevented weight gain, reduced waist circumference and visceral fat compared with Pio + ADA diet.